Anxiety, depression, and quality of life in postoperative non-small cell lung cancer patients under the intervention of cognitive-behavioral stress management - Wang, Fengju; Zhang, Shuyan; Song, Bingbing; Han, Yuxiang (Frontiers in Psychology, 2023)
Objective: Cognitive-behavioral stress management (CBSM) is a psychotherapy that helps patients cognize and manage stress to improve mental health and quality of life. This study aimed to explore the influence of CBSM on anxiety, depression, and quality of life in non-small cell lung cancer (NSCLC) patients. Methods: In total, 172 NSCLC patients who received tumor resection were randomized 1:1 into the usual care (UC) group (N=86) and CBSM group (N=86) to receive 10-week UC and CBSM interventions. Moreover, all participants attended a 6-month follow-up. Results: Hospital Anxiety and Depression Scales (HADS)-anxiety score at 3rd month (M3) (P=0.015) and 6th month (M6) (P=0.018), HADS-depression score at M3 (P=0.040) and M6 (P=0.028), and depression rate at M6 (P=0.035) were descended in CBSM group compared to UC group. Besides, depression severity was reduced at M6 (P=0.041) in CBSM group compared to UC group, but anxiety severity only showed a decreased trend (P=0.051). Additionally, Quality of Life Questionnaire-Core 30 (QLQ-C30) global health status score and QLQ-C30 function score at 1st month (M1), M3, and M6 were elevated (all P<0.05), while QLQ-C30 symptoms score was declined at M1 (P=0.031) and M3 (P=0.014) in CBSM group compared to UC group. Notably, the efficacy of CBSM was impressive in patients with baseline depression or undergoing adjuvant therapy. Conclusion: CBSM is a feasible intervention that effectively improves mental health and quality of life in postoperative NSCLC patients.